VILLAGE MANAGEMENT BASED ON CIVIC LEADERSHIP IN BUILDING PUBLIC ETHICS AT THE LOCAL LEVEL - Kolo, Adriana; Iqbal, Asep (Yayasan Pendidikan Cahaya Budaya Indonesia, 2025)
This article provides an in-depth examination of the correlation between civic leadership, the role of Pancasila education, and village management in fostering public ethics at the local level, namely the village. Following the implementation of decentralization and the disbursement of substantial funds, villages have become crucial entities in enhancing citizens’ participation and engagement in regional development. However, villages have also become spaces that inherently hold the potential for irregularities—ranging from abuse of authority and weak transparency to public skepticism toward village governance—ultimately leading to a decline in community participation. Using a theoretical approach, this article offers a comprehensive conception of village management, in which village leadership is not merely an administrative function but also a manifestation of civic values. Pancasila education serves as a catalyst for social transformation that can strengthen the values of responsibility, integrity, democracy, and leadership.